(untitled) (Journal of the College of Education for Women, 2022)
The research deals with a very important issue that affects women, an important segment of the society. This is because women are the basis of the family and the pillar of the society. Thus, the aim of the research is to examine the level and dimensions of the emotional and existential psychological crisis at the sample of the study. It further aims to investigate the statistical significant difference at the level of (0.05) regarding the feeling of the existential psychological crisis among battered and non-battered women. To reveal the objectives of the study, the researcher applied the existential psychological crisis scale to a sample of (72) women, divided into two groups: (35) battered women, who have been chosen purposefully. Those women reside in the protection homes of the Yemeni Women’s Union, or are from civil society associations as Sama and Shaima. The control group consisted from (37) non-battered women. The study has revealed that there are statistically significant differences at the level of (0.01), where all dimensions are significant except the third dimension. Besides, there has been a high level of existential psychological crisis among the women, who have been exposed to violence. Thus, there are statistical significant differences regarding the level of psychological crisis at all dimensions at the level (0.01). The results have further revealed the existence of differences between the computed averages of feeling of the psychological crisis at both groups. This is because the values of t-test of both groups are independent and significant at the level (0.01) in favor of the battered women. This indicates that such a psychological crisis among these women is high.